The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1464-5491.2005.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manipulation of basal pulsatile insulin on insulin action in Type 2 diabetes

Abstract: There was no demonstrable priming effect derived from overnight pulsatile insulin compared with constant insulin infusion on subsequent insulin sensitivity in Type 2 diabetic subjects. The failure of 7-min pulses to exhibit an advantageous effect over 13-min pulses raises questions about the natural frequency of basal insulin pulses and their biological effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies in animal models have suggested that pulsatile insulin delivery is superior in suppressing hepatic glucose output than continuous insulin administration . Studies comparing pulsatile vs. continuous insulin administration in humans are controversial , which might in part be explained by the fact that the endogenous route of intraportal insulin delivery cannot readily be mimicked by peripheral intravenous (i.v.) insulin administration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in animal models have suggested that pulsatile insulin delivery is superior in suppressing hepatic glucose output than continuous insulin administration . Studies comparing pulsatile vs. continuous insulin administration in humans are controversial , which might in part be explained by the fact that the endogenous route of intraportal insulin delivery cannot readily be mimicked by peripheral intravenous (i.v.) insulin administration.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated the effect of overnight pulsatile versus continuous basal insulin infusions on insulin action measured during a clamp test administered in the morning. In subjects with and without diabetes, they found no priming effect of basal pulsatile insulin on glucose uptake during the clamp 68,69 …”
Section: Effects Of Pulsatile Insulin Secretion On Insulin Actionmentioning
confidence: 94%
“…In subjects with and without diabetes, they found no priming effect of basal pulsatile insulin on glucose uptake during the clamp. 68,69 On the other hand, the importance of the pulsatile release pattern in regulating physiologic insulin action can be appreciated from experimental models demonstrating that the response of key phosphorylation events in the insulin signaling cascade in the fed state are robust when primed by fasted insulin pulses. It appears that pulses in the fasted state create a memory that sensitizes the signaling in the fed state.…”
Section: Effects Of Pulsatile Insulin Secretion On Insulin Actionmentioning
confidence: 99%